2020
DOI: 10.1155/2020/6340190
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Attenuates Abdominal Aortic Aneurysm Formation Favoured by Lack of Nrf2 Transcriptional Activity

Abstract: Surgical intervention is currently the only option for an abdominal aortic aneurysm (AAA), preventing its rupture and sudden death of a patient. Therefore, it is crucial to determine the pathogenic mechanisms of this disease for the development of effective pharmacological therapies. Oxidative stress is said to be one of the pivotal factors in the pathogenesis of AAAs. Thus, we aimed to evaluate the significance of nuclear factor erythroid 2-related factor 2 (Nrf2) transcriptional activity in the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…The infusion of a high dose of AngII led to the formation of AAA in around 80% of animals. The frequency of appearance was significantly greater than in the case of the standard dose (Fisher’s exact test, p < 0.05), which led to the formation of AAA in 30–40% of mice, as reported by several groups, including us [ 18 ] ( Figure 1 C). Detailed morphological analysis and grading revealed the development of a wide range of aneurysms in high-dose AngII, varying from type 1 dilated AAA, through most common type 3 dissected, up to type 5-ruptured ( Figure 1 D).…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…The infusion of a high dose of AngII led to the formation of AAA in around 80% of animals. The frequency of appearance was significantly greater than in the case of the standard dose (Fisher’s exact test, p < 0.05), which led to the formation of AAA in 30–40% of mice, as reported by several groups, including us [ 18 ] ( Figure 1 C). Detailed morphological analysis and grading revealed the development of a wide range of aneurysms in high-dose AngII, varying from type 1 dilated AAA, through most common type 3 dissected, up to type 5-ruptured ( Figure 1 D).…”
Section: Resultssupporting
confidence: 72%
“…Thus, we decided to inspect those parameters. Basing on our previous experience [ 18 ], and bearing in mind that aneurysms are formed by day 14, we focused on day 14 after implementation of osmotic pumps. We found that enhanced inflammatory response and oxidative imbalance are distinctive features of an aneurysm itself.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations